2010
DOI: 10.1016/j.stem.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Lgr5+ve Stem Cells Drive Self-Renewal in the Stomach and Build Long-Lived Gastric Units In Vitro

Abstract: The study of gastric epithelial homeostasis and cancer has been hampered by the lack of stem cell markers and in vitro culture methods. The Wnt target gene Lgr5 marks stem cells in the small intestine, colon, and hair follicle. Here, we investigated Lgr5 expression in the stomach and assessed the stem cell potential of the Lgr5(+ve) cells by using in vivo lineage tracing. In neonatal stomach, Lgr5 was expressed at the base of prospective corpus and pyloric glands, whereas expression in the adult was predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
1,449
4
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 1,357 publications
(1,512 citation statements)
references
References 35 publications
48
1,449
4
11
Order By: Relevance
“…Furthermore it has also been reported that the murine small intestinal and colonic crypt base columnar cells (CBCs) expressing lgr5, are actively cycling and are able to regenerate the entire cell population. 1,[20][21] We have also shown LGR5 mRNA is expressed in LRC region of the Barrett's mucosa in man.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore it has also been reported that the murine small intestinal and colonic crypt base columnar cells (CBCs) expressing lgr5, are actively cycling and are able to regenerate the entire cell population. 1,[20][21] We have also shown LGR5 mRNA is expressed in LRC region of the Barrett's mucosa in man.…”
Section: Discussionmentioning
confidence: 53%
“…Fifth even the relatively simple question of the location of stem cells in the normal stomach and esophagus in man have not been previously proposed, although data is available in animal models. Despite these problems other techniques which trace lineage by genetic analyses strongly favour the likelihood of common stem cells between squamous and columnar esophageal mucosa [19][20][21][22][23][24] . The site of stem cells in BE has been more problematic [10][11][12][13][14][15] as well as the availability of true 'biomarkers' of stem cells [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…The niche environment centers around the crypt base Lgr5-positive stem cells that divide into both daughter stem cells and transit-amplifying (TA) cells committed to differentiation. Although the direction of these divisions as a population is random, and the number of stem cells remains relatively constant through all divisions, it appears that location in the crypt determines whether a stem cell produces more stem cells or differentiates (Lopez-Garcia et al 2010;Snippert et al 2010;Ritsma et al 2014;Walther and Graham 2014).…”
Section: Intestinal Stem and Progenitor Cellsmentioning
confidence: 99%
“…2). Using combinations of these factors, organoids can be cultured from mouse stomach small intestine and large intestine [45][46][47][48][49], as well as from healthy human colon cells and CRCs [47,49,50]. Moreover, organoids can be initiated not only from rapidly cycling Lgr5 stem cells but also from slowly cycling Bmi1 stem cells [28,30,33].…”
Section: Organoids: 3-dimensional Mini-guts In a Dishmentioning
confidence: 99%